Comparison Between Consumer Education Laws in Indonesia and Singapore - Ronaldo Heinrich Herman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This research aims to emphasize the importance of consumer protection in Indonesia. Law No. 9 of 1999 regulates the consumer's right to education. However, the legal norms for consumer protection do not regulate in detail the knowledge that should be taught. The position of consumers becomes weaker, making them vulnerable to fraud. Any loss suffered constitutes a violation of the objectives of the Consumer Protection Act in Indonesia. Consumer conditions in Indonesia are different from those in Singapore. The 2009 Consumer Protection (Fair Trading) Act does not specifically regulate consumer education materials. However, the Consumers Association of Singapore (CASE) actively provides education to consumers in Singapore. This research will compare the consumer education in Indonesia and Singapore. The comparative results will lead this research to suggestions for legislative power holders regarding how consumer education laws should be drafted and implemented in Indonesia.